2017
DOI: 10.1186/s12868-017-0348-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Spp1 on nerve degeneration and regeneration after rat sciatic nerve injury

Abstract: BackgroundWallerian degeneration (WD) in injured peripheral nerves is associated with a large number of up- or down-regulated genes, but the effects of these changes are poorly understood. In our previous studies, we reported some key factors that are differentially expressed to activate nerve degeneration and regeneration during WD. Here, we determined the effects of secreted phosphoprotein 1 (Spp1) on WD after rat sciatic nerve injury.ResultsSpp1 was upregulated from 6 h to 14 days after sciatic nerve injury… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 41 publications
(30 reference statements)
1
30
0
Order By: Relevance
“…These provided the scienti c basis for our following experiment and also provided a theoretical foundation for the clinical transformation of experimental research. Intriguingly, we found that the expression pattern of SPP1 and PKCα after median nerve injury in clinical cases was a little bit different from the performance of the injured sciatic nerve injury in rats [23,24], but the overall upward trend was consistent. This suggests that there are differences between human and rat, which should be considered in future studies.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…These provided the scienti c basis for our following experiment and also provided a theoretical foundation for the clinical transformation of experimental research. Intriguingly, we found that the expression pattern of SPP1 and PKCα after median nerve injury in clinical cases was a little bit different from the performance of the injured sciatic nerve injury in rats [23,24], but the overall upward trend was consistent. This suggests that there are differences between human and rat, which should be considered in future studies.…”
Section: Discussionmentioning
confidence: 73%
“…As both SPP1 and PKCα promoted cell proliferation and inhibited cell apoptosis of SCs, and silence of SPP1 resulted in the reduced PKCα [23], we proposed that SPP1 might function through PKCα. To check this hypothesis, we rstly introduced si-SPP1 to knockdown and GV146-SPP1 to overexpress of SPP1 in primary cultured SCs.…”
Section: Spp1 Promoted Sc Proliferation and Inhibited Apoptosis Throumentioning
confidence: 88%
See 1 more Smart Citation
“…All animals underwent surgery to establish the sciatic nerve injury model as previously described (Liu et al, 2017 ). We randomly divided the rats into six groups and performed the operation (Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…The immune microenvironment of injured nerves plays a critical role in the regulation of nerve regeneration after injury 5,6 . Debris resulting from degenerated axons and myelin can inhibit axonal regrowth and should be cleared to create a favorable microenvironment for subsequent nerve regeneration 7 .…”
Section: Introductionmentioning
confidence: 99%